PENAMBAHAN PROBIOTIK Bacillus subtilis DALAM PAKAN TERHADAP BERAT TELUR, TINGGI ALBUMEN, DAN HAUGH UNIT PADA AYAM PETELUR: PENAMBAHAN PROBIOTIK Bacillus subtilis DALAM PAKAN TERHADAP BERAT TELUR, TINGGI ALBUMEN, DAN HAUGH UNIT PADA AYAM PETELUR - huda, khoirul (VITEK : Bidang Kedokteran Hewan, 2023)
The increasing need for protein, both meat and eggs, still continues to increase. Antibiotics addition can increase egg growth and production. Based on Law No.18 of 2009 along with Law No.41 of 2014 concerning existing livestock, there is a prohibition on the use of antibiotics mixed with feed. The use of probiotics mixed with feed, is used to increase livestock productivity. This study aims is to determine the effect of Bacillus subtilis probiotics addition on egg weight, albumen height and haugh unit values. 18 Laying hens aged 39 weeks were randomized into 3 treatments with 8 reiterations. The treatment consisted of P0 without the addition of probiotics, P1 with the addition of Bacillus subtilis 0.1 gram / kg of feed probiotics and P2 with the addition of Bacillus subtilis 0.2 gram / kg of feed probiotics. The results of the analysis using the test (ANOVA) showed a significant difference (p <0.05) to the egg weight value, the albumen height values were significant (p <0.05) and (p <0.05) in the haugh unit value . In conclusion the addition of probiotics in concentrations of 0.1 and 0.2 grams can increase the value of egg weight, albumen height and haugh unit.